An Analysis on the Positive Solutions for a Fractional Configuration of the Caputo Multiterm Semilinear Differential Equation. (23rd June 2021) - Rezapour, Sh.; Azzaoui, B.; Tellab, B.; Etemad, S.; Masiha, H. P.
Abstract : In this paper, we consider a multiterm semilinear fractional boundary value problem involving Caputo fractional derivatives and investigate the existence of positive solutions by terms of different given conditions. To do this, we first study the properties of Green's function, and then by defining two lower and upper control functions and using the wellknown Schauder's fixed-point theorem, we obtain the desired existence criteria. At the end of the paper, we provide a numerical example based on the given boundary value problem and obtain its upper and lower solutions, and finally, we compare these positive solutions with exact solution graphically.